A STATISTICAL APPROACH TO DETERMINING TARGETED SUBSIDY AMOUNTS BASED ON ENERGY CONSUMPTION IN INDONESIA - Fernando, Very; Rusadi, Widya A; Ernes, Risa Nadia; Wirawan, Nanda Tommy (Ensiklopedia of Journal, 2025)
Energy subsidies are an important government policy to ensure affordable energy access for the public, especially for underprivileged groups. However, determining the appropriate subsidy amount is often inaccurate. This study proposes a statistical approach based on the Probability Density Function (PDF) and Cumulative Distribution Function (CDF) to analyze energy consumption patterns in society, covering electricity, fuel (BBM), and gas. This method aims to identify the distribution of energy consumption across different social groups to enable more accurate classification of subsidy recipients. The PDF analysis is used to evaluate the probability of energy consumption within a specific range, while the CDF is utilized to determine the consumption threshold that serves as the basis for setting subsidy values. Using three energy variables (electricity, fuel, and gas), fuel consumption accounts for the largest percentage, ranging from 60-70% of total energy consumption among non-affluent households, with an average total expenditure between 330,000 to 480,000 per month. Subsidies can be directly allocated in the form of cash for energy needs, thereby improving subsidy allocation efficiency by PLN and Pertamina. Keywords : energy subsidies, energy consumption, PDF, CDF, subsidy allocation